Non-governmental actors in international climate change law : the case of arctic indigenous peoples - Scopelliti, Marzia (New York: Routledge, 2022)
'Focusing on how to improve the participation of non-governmental actors in the making of international climate change laws, this book is a conversation on the relevance of a human rights-based approach to international climate change law-making. Due to the relevance of the addressed subject, the book is destined to a broad readership and will be of use to academic researchers, law practitioners, policy-makers and non-governmental organisations' representatives'--
Introduction -- International environmental governance and non-governmental actors -- The participation on non-governmental actors in climate change law-making and governance -- Non-governmental actors and a changing climate : learning from Arctic Indigenous peoples -- Climate change litigation : a bottom-up approach to climate change governance -- A human rights-based approach to climate change : improving the participation of non-governmental actors in international climate change law-making -- Concluding remarks-towards a new significance for non-governmental actors in international climate change governance : a proposal for the future.
Includes bibliographical references and index. (151-159 pages)
Puan Shaizimah Badzri/ Ketua Perpustakaan Undang-Undang/ shai@ukm.edu.my/ 6393/ Pemilihan Ketua Perpustakaan Undang-Undang/ OC/ Bookline Services
Keywords: Climatic changes -- Law and legislation; Non-governmental organizations -- Law and legislation; Environmental law, International